Resilience based optimization for pressurized distribution networks - Hadeel Ahmed Tarek ElShaboury; Mostafa Ghaith; Tarek Salaheldin (2024)
The research focuses on Pressurized Distribution Networks (PDNs), vital for public health and safety. Resilient PDNs manage unforeseen population surges, ensuring uninterrupted water supply amidst demographic shifts. Prior studies mainly addressed PDN design as a least-cost optimization problem, lacking multi-criteria decision-making techniques. Addressing these gaps, the thesis develops a holistic multi-objective optimization model. Genetic Algorithm, Salp Swarm Algorithm, Dragonfly Algorithm, and Strength Pareto Evolutionary Algorithm II are employed for optimal design alternatives. Performance metrics comparison reveals the Dragonfly Algorithm as superior. Multi-criteria decision-making models, including Technique for Order Preference by Similarity to Ideal Solution and Multi-Objective Optimization on the basis of Ratio Analysis, are applied to rank near-optimal designs. Spearman correlation coefficient confirms their close connection. The framework is validated using a benchmark network then applied the developed model on a real case study in Egypt for both cases: single and multi-objective optimization models. This research aids planners in assessing and enhancing PDN resilience and strategizing for resilient PDNs
(3JYO GdEOGQI GdaYGdI dTHcGJ GdJhRjY GdeVZhWI CeQkG VQhQjkG, NGUI aj GdGQJaGYGJ ZjQ GdeJhbYI aj YOO GdScGf, eeG jVef JhajQ GdejGg HTcd eJhGUd hSW GdJMhdGJ GdOjehZQGajI(B. (3hfJjLI dPdc, XgQ eaghe GdeQhfI ddJYGed eY GdGVWQGHGJ GdJj CUHMJ CcKQ JcQGQkG(B. (3Je JUeje GdTHcGJ GdeQfI dJMed GdeNGWQ GdeNJdaI hGdJYGaj efgG, eeG jVef MSf SjQ GdYed(B. (3JWhQ gPg GdQSGdI EWGQ TGed dJbjje GdeQhfI hGdJcdaI ddTHcGJ, eY GdCNP aj GdGYJHGQ GdYOjO ef GdbjhO(B. (3jSJNOe GdEWGQ GdebJQM CQHY NhGQRejGJ dJRhjO GdeNWWjf HHOGFd JUejejI eecfI(B. (3hjJe ELQGA ebGQfI Ydi GdfJGFL HGSJNOGe CQHYI ebGjjS ddCOGA(B. (3jJe JfajP fhYjf ef JbfjGJ GJNGP GdbQGQ eJYOO GdeYGjjQ dJUfja GdHOGFd GdJj Je GdMUhd YdjgG ef fbGW MOhO HGQjJh(B. (3jJe GdJMbb ef UMI GdEWGQ HGSJNOGe THcI eQLYjI hJWHjb GdfehPL GdeWhQ Ydi OQGSI THcI aj eUQ aj cd ef feGPL GdJMSjf PGJ GdgOa GdhGMO heJYOOI GdCgOGa(B.s
Thesis (M.Sc)-Cairo University, 2024.
Bibliography: pages 91-104.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Hydraulic engineering; (3gfOSI GdQjs; Pressurized distribution networks -- Optimization -- Cost -- Resilience -- Meta-heuristic algorithms